Improvement in tricuspid regurgitation following catheter ablation of atrial fibrillation. (14th August 2020) - Markman, Timothy M.; Plappert, Theodore; De Feria Alsina, Alejandro; Levin, Michael; Amankwah, Nigel; Sheth, Samip; Gertz, Zachary M.; Schaller, Robert D.; Marchlinski, Francis E.; Rame, Jesus E.; Frankel, David S.
Abstract: Introduction: Functional tricuspid regurgitation (TR) remains a challenging clinical problem with poor outcomes and few effective treatments. Atrial fibrillation (AF) has been associated with functional TR. We sought to determine whether restoring sinus rhythm through catheter ablation of AF can decrease the degree of TR. Methods and Results: A retrospective cohort study of patients undergoing AF ablation between 2011 and 2017 at a single center was conducted. We included patients with at least moderate TR on echocardiogram within the year preceding ablation, who underwent repeat echocardiogram within the year following ablation. Formal quantitative analysis was performed by an experienced research echocardiographer, blinded to arrhythmia outcomes. Arrhythmia‐free survival was correlated to the extent of improvement in TR. Thirty‐six patients met the inclusion criteria. A baseline echocardiogram was performed 37 ± 68 days before ablation and follow‐up echocardiogram 139 ± 112 days following ablation. Patients were 63.7 ± 11.1 years old with a mean CHA2 DS2 ‐VASc score of 2.7 ± 1.7. The degree of TR improved by at least one grade in 23 patients (64%). TR area decreased from 11.6 ± 3.4 to 7.0 ± 3.5 cm 2 ( p  < .001) following ablation. Freedom from AF postablation was associated with a greater likelihood of improvement in TR by at least one grade (100% vs. 41%, p  = .02). Conclusions: In patients with AF and at least moderate TR, catheter ablation is associated with substantial improvement in TR severity.